Trade-off custo-qualidade na provisão de serviços públicos: comparação entre os modelos de provisão de saneamento básico no Brasil e efeitos sobre a saúde - Oliveira, Welber Tomás de (2019)
This thesis investigated three hypotheses regarding the provision of basic sanitation services in Brazil - water supply and sewage - which are: i) whether there is a trade-off between cost and quality; ii) if the private provision accentuates it; (iii) whether the provision by hybrid models may mitigate it. For such, panel data models are estimated, in which indicators of hospital morbidity due to diseases directly associated with sanitation are dependent variables, being a proxy for non-contractible quality of sanitation services. The results show that, in line with to the model of Hart et al. (1997) and characteristics of the water sector, it is not possible to reject the hypothesis of a trade-off between cost and quality in the sector. However, the provision by private models does not accentuate this relationship; but the provision by hybrid models has the characteristic of accentuating it.